In situ remediation of atrazine contaminated groundwater - Pearson, Robert (Cranfield University, 2006)
The natural attenuation of groundwater pesticides by biological degradation, is widely accepted to occur at concentrations > 1 mg 1-1. However from observations of groundwater monitoring data it can be indicated that the occurrence of pesticides in groundwater is primarily at trace μg 1-1 concentrations, with 45 % of UK groundwater samples that failed the EC Drinking Water Directives PV of 0.1 μg 1-1 between 1995 – 2000, accounting for an average concentration of 64 μg 1-1. However, there are limited directed studies of in situ biological degradation of pesticides at μg concentrations. Therefore, this work was designed provided an insight as to whether any prevalent microbial adaptation can occur to degrade atrazine at μg 1-1 concentrations in groundwater. Laboratory batch studies were performed using a groundwater exposed to 0.2 μg 1-1 of the herbicide atrazine, for an excess of 10 years. Bacterial enrichment using a glucose minimal salts medium resulted in no biological degradation of atrazine, when amended at concentrations between 10 μg to 50 mg 1-1. Batch studies using the atrazine degrader Pseudomonas sp. Strain ADP as a positive control, indicated a capability to degrade atrazine within sterilised groundwater, at 50 mg 1-1 (0.92 mg 1-1 day-1) and 1 mg 1-1 (0.14 mg 1-1 day-1), but no degradation of atrazine at 100 or 10 μg 1-1. Therefore, biological degradation of trace μg 1-1 concentrations of atrazine by groundwater in situ bacteria does not readily occur. It is expected that changes in atrazine groundwater concentrations, are resulting purely from dilution, sorption or chemical degradation. Consequently, it cannot be assumed that microbial adaptation can occur to degrade atrazine at μg 1-1 concentrations in groundwaters even if in situ bioaugmentation methods are applied.